Identification of Antibacterial Efficacy of Cb6 (E)-1-(4-fluorophenyl)-3-Phenylprop-2-en-1-one against Escherichia Coli - Nimra Arshad, Haris Abdul Rehman, Hafiz Khawar, Muhammad Umar, Rabia Khurshid, Misbah Faiz, Aqsa Qurban, Kanza Batool, Hafiza Rumesa Yaqoob, Dania Azeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective of the study: Escherichia coli bacteria with increased antibiotic resistance represent a serious threat to public health. The aim of this study was to assess Cb6 (E)-1-& effectiveness against microorganisms (4-fluorophenyl), determine the effectiveness of Cb6 (E)-1-(4-fluorophenyl)-3-phenyl prop-2-en-1-one against anti-fungal agents and -3 -phenylprop-2-en-1-one against E. coli (Curvularia). StudyDesign:Study was designed by sample collection, culturing, biochemical tests, sensitivity assay and qRT-PCR. Place and Duration: The prospective study was carried out at the University of Agriculture in Faisalabad, Pakistan from 1st February 2019 to 18th June 2019. Methodology: Through horizontal and vertical gene transfer, Escherichia coli acquired resistance genes and developed resistance against many antibiotic classes. The following genes were examined in the current study in E. coli: Van B, ermC, Iva-A, Qnr-A, Qnr-B, tet M, tet O, and tet W resistance genes. To assess the effectiveness of the antibacterial and antifungal agents, antibiotic sensitivity testing was carried out. Results: E.coli chalcone resistance genes, have displayed highly significant (P 0.0001) expression in the patient sample when compared to the control. Conclusion: It was concluded that the chalcones are highly resistant to E coli in prediction. Van B, erm C, Iva-A, Qnr-A, Qnr-B, tet M, tet O, and tet Ware resistant genes of the Escherichia coli against the Cb6 (E)-1-(4-fluorophenyl)-3 -phenyl prop-2-en-1-one and it was showed the high expression level. Keywords: Chalcones Resistant gene, Antibacterial action, Antibiotic sensitivity, Expression.